Review on Psoriasis and Their Managments - Tejaswini G.Khonde; Sakshi P. Waikar; Nilakshi N. Dhoble; Nitin Padole; Pankaj Dhapke; Jagdish R. Baheti (Asian Journal of Pharmaceutical Research and Development, 2024)
Psoriasis (PSO) is a chronic autoimmune skin condition characterized by the rapid and excessive growth of skin cells, which leads to the formation of thick, red, and scaly patches on the surface of the skin. These patches can be itchy and painful, and they may cause discomfort for patients affected by this condition. The pathogenesis of psoriasis includes genetics, environmental factors, lifestyle causes. Diagnosis of psoriasis can be done by self-examination or skin biopsy and in some cases differential diagnosis may be required. Therapies for psoriasis aim to alleviate symptoms, reduce inflammation, and slow down the excessive skin cell growth. Psoriasis cannot be cured but there are effective treatment options available. Attempts have been made in this review to focus on the etiology, pathophysiology, diagnostic methods and treatment options which may be used for psoriasis patients worldwide.